Development and learning: a historical-cultural approach - Melo, Eliane Pimentel Camillo Barra Nova de (Revista Hipótese, 2018)
The following work titled Development and learning: an historic-cultural approach seeks to conceptualize development and learning according to Vygostsky and his colaborators theories. It is a bibliography research that resulted, concomitanly, in the distinction and interrelation of two concepts: development and learning, the first one standing as a biological issue, the second as a socio-cultural one. Thus, according to the historic-cultural approach, the human mind is socially formed by interpersonal relations and biological development, although development is necessary for learning, it is leveraged by the process of learning itself. Hence the human cognition is constitued by biological integrity and interrelation with socio-cultural environment the human being lives. Therefore a prospective and positive vision of the cognitive ability of every person is allowed.
Keywords: Development; Learning; Historic-cultural